2019
DOI: 10.1039/c9ra01258c
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic foam prepared from high internal phase emulsion templates stabilised by oyster shell powder for oil–water separation

Abstract: Poly(styrene-divinylbenzene) foam was synthesized through a high internal phase emulsion (HIPE) technique with Span 80 and superfine oyster shell powder as a co-emulsifier, and the foam exhibited excellent superhydrophobicity and oleophilicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
15
1
Order By: Relevance
“…Among these SPE adsorbents, MOFs were possessed of high adsorption and separation performance, owing to their remarkable merits like large surface area, adjustable pore size, diverse structures, as well as great chemical and thermal stability. [19][20][21] On the other hand, polyHIPEs were also highly interconnected porous materials with distinct characteristics such as highly interconnected pore architecture, tunable porosity, controllable cavity, large surface areas, and adjustable functions, [22][23][24] however, depending on the high porosity poly-HIPEs for separation applications usually suffer from insufficient mechanical properties (strength, modulus and ductility). [25][26][27] Thus, enhancement of mechanical properties by using a variety of approaches, such as selecting new functional monomer systems, using medium internal phase emulsions instead of HIPEs to obtain higher density polyHIPEs, and especially combining HIPE templates with organic or inorganic particles to form composite structures, was very important to achieve improved polyHIPEs for separation applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among these SPE adsorbents, MOFs were possessed of high adsorption and separation performance, owing to their remarkable merits like large surface area, adjustable pore size, diverse structures, as well as great chemical and thermal stability. [19][20][21] On the other hand, polyHIPEs were also highly interconnected porous materials with distinct characteristics such as highly interconnected pore architecture, tunable porosity, controllable cavity, large surface areas, and adjustable functions, [22][23][24] however, depending on the high porosity poly-HIPEs for separation applications usually suffer from insufficient mechanical properties (strength, modulus and ductility). [25][26][27] Thus, enhancement of mechanical properties by using a variety of approaches, such as selecting new functional monomer systems, using medium internal phase emulsions instead of HIPEs to obtain higher density polyHIPEs, and especially combining HIPE templates with organic or inorganic particles to form composite structures, was very important to achieve improved polyHIPEs for separation applications.…”
Section: Introductionmentioning
confidence: 99%
“…The oil adsorption capacity was improved compared to other studies. 23,51 This indicated that the material has a good saturation adsorption capacity.…”
Section: Oil Adsorption Capacity and The Reusability Of The Foammentioning
confidence: 89%
“…The hydrophobicity of the foam prepared in this work is greater than that mentioned in the previous reports. 23,42 However, as the content of PZS microspheres was more than 15%, the contact angle gradually decreased. It might be inferred from the material's microstructure that PZS microspheres were easy to be agglomerated when PZS content is too high, destroying the micro and nanostructures.…”
Section: Hydrophobicity Of the Foammentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, the compounds of mercaptan and bivalent copper [23,24] were prepared and then covered in the surface of PU sponge [25], so that the sponge had the superhydrophobicity. It is also found that superhydrophobic sponge has excellent performance in oil and water separation [26].…”
Section: Introductionmentioning
confidence: 99%